As estratégias utilizadas por crianças em fase de apropriação da leitura: uma análise baseada na interação com instrumentos de avaliação em larga escala - Oliveira, Joyce Carneiro de (2012)
About twenty years, Brazilian’s government has used large-scale evaluation systems and programs such a way to understand and act in the education. In the year 2007 the “Programa de Alfabetização na Idade Certa” - PAIC has brought a new view over this evaluations, promoting a diagnose of the children’s skills, specifically that ones that were in the process of literacy’s construction, in the sense of bring to the teacher the individual performance of his students, from their abilities of reading and writing included in the tests. During the PAIC’s activities, for a little more than 3 years (2008-2011) specifically in the Axe of the External Evaluation has possible to see the need to understand the ways that the students traveled in the moment that they answered the items of the tests of the program, as soon the learning process was better understood, and besides was possible to build evaluation tools consonant to evaluated children thoughts. In this meaning, this work has as the purpose to identify and to analyze the strategies used by children in construction of reading from the interaction with the large-scale evaluation’s instruments. As methodology, were chosen the qualitative research of the review of references, the analysis of documents and the field research. The data was collected through the analysis of the documents, review of references and interviews with 70 children, enrolled at a school that belongs to the municipal administration of Maracanaú – Ceará, that were submited to the “Provinha do PAIC” in the year 2011. The interviews were conducted by the clinical experimental method of Jean Piaget. More then the “Provinha do PAIC” of the year 2011, was used to collect data an instrument elaborated in the same manners of an external evaluation test with reading competence abilities that is able to evaluate the reading of phrases, the location of explicit and implicit information in a text, and recognizing the final purpose of a text and the subject of it. The research presented as general results the following points: 1) 13 reading strategies were identified and analyzed; 2) Children that were phrase readers were not able to read words; 3) The Reading strategies can elucidate the necessary pedagogical interventions in a specific classroom, beyond the items elaborations technics; 4) Previous knowledge and emotional links can determine the answers of school-age children; 5) Among the abilities of text understanding the one that has presented more difficult was the text recognizing. The research, at last, has found evidences that by the large-scale evaluation tests is possible to identify the reading strategies elaborated by children, since formative evaluation elements were incorporated.